1998
DOI: 10.1021/bi981300k
|View full text |Cite
|
Sign up to set email alerts
|

Topology of the Thyroid Transcription Factor 1 Homeodomain−DNA Complex

Abstract: The topology of the thyroid transcription factor 1 homeodomain (TTF-1HD)-DNA complex was investigated by a strategy which combines limited proteolysis and selective chemical modification experiments with mass spectrometry methodologies. When limited proteolysis digestions were carried out with the protein in the absence or presence of its target oligonucleotide, differential peptide maps were obtained from which the amino acid residues involved in the interaction could be inferred. Similarly, selective acetyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…Consequently, covalent labeling of lysine residues along with MS detection has been used effectively to study protein-nucleic acid interactions, which are particularly important to regulate DNA replication and transcription. The surface topology of the thyroid transcription factor 1 homeodomain (TTF1HD)-DNA complex was characterized by Scaloni et al who used a combination of limited proteolysis, selective acetylation with acetic anhydride, and MS analysis (Scaloni et al, 1999). MALDI-TOF MS and limited proteolysis revealed that the N-terminus, Lys4, and Lys25 were acetylated in the isolated protein but not in the TTF1-HD-oligonucleotide complex; that difference indicated that there is a structural change in these regions upon interaction with DNA.…”
Section: Amino Acid-specific Labels and Examples Of Their Applicmentioning
confidence: 99%
“…Consequently, covalent labeling of lysine residues along with MS detection has been used effectively to study protein-nucleic acid interactions, which are particularly important to regulate DNA replication and transcription. The surface topology of the thyroid transcription factor 1 homeodomain (TTF1HD)-DNA complex was characterized by Scaloni et al who used a combination of limited proteolysis, selective acetylation with acetic anhydride, and MS analysis (Scaloni et al, 1999). MALDI-TOF MS and limited proteolysis revealed that the N-terminus, Lys4, and Lys25 were acetylated in the isolated protein but not in the TTF1-HD-oligonucleotide complex; that difference indicated that there is a structural change in these regions upon interaction with DNA.…”
Section: Amino Acid-specific Labels and Examples Of Their Applicmentioning
confidence: 99%
“…A similar study probed the topology of the thyroid transcription-factor 1 homeodomain by limited proteolysis and chemical modification experiments combined with electrospray ionization-MS (ESI-MS) and MALDI (Scaloni et al, 1999). Limited proteolysis of the apo-form and of the DNA-bound transcription factor, in addition to lysine-acetylation protection experiments, provided a structural model that was consistent with the known 3-dimensional structure previously obtained by NMR.…”
Section: Structural Characterization Of Transcription Factorsmentioning
confidence: 53%
“…37,38 We have also successively used this kind of approach to study the topology of a HD containing transcription factor (ie TTF-1) bound to DNA 39 and found strong similarities with data obtained by NMR studies. 40 It is known that trypsin cleaves at the C-terminal sides of both the Lys and Arg residues of proteins; therefore, we speculated that mutations affecting Arg residues would alter the trypsin proteolytic pattern of the PAX6 mutant.…”
Section: Sensitivity To Trypsin Digestionmentioning
confidence: 65%